Clinical Practice Guidelines for Acute Renal Failure. - Argelio Alberto Santana Cano; Marta Patricia Casanova González; Belkys Rodríguez Llerena; Eddy Pereira Valdés (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Acute Renal Failure. It a syndrome characterized by the abrupt deterioration of basal renal functions (abrupt reduction of glomerular filtration) and the consequent increase of nitrogenous products in the blood as well as the homeostasis of the body. It aetiological agents, clinical presentation, therapeutic and diagnostic methods are described. It includes assessment guidelines focused on the most important aspects to be accomplished.